Epigenetic modifiers and minerals as tools to diversify secondary metabolite production in fungi - Siti Hajar Sadiran,; Fatmawati Lambuk,; Siti Nur Sarah Zubir,; Suliman, Rasha Saad; Weber, Jean-Frédéric Faizal (Penerbit Universiti Kebangsaan Malaysia, 2022)
Secondary metabolite production of fungi can be modified by different approaches, including epigenetic modifiers, culture-dependent methods, and genomic-based methods. In this study, secondary metabolite production was explored in the presence of epigenetic modifiers and minerals using a microscale fermentation approach. Thirteen fungi originally isolated from mushrooms and soils were grown in 96-well microtiter plates (MTPs) using 70% of potato dextrose broth (PDB) with the addition of epigenetic modifiers and minerals in different combinations and concentrations. All cultures were fermented at 10 °C or 28 °C for 2, 3, or 5 weeks and extracted by solid phase extraction. The resulting extracts were subjected to high-performance liquid chromatography (HPLC) and the chromatograms were analyzed on a qualitative and quantitative basis. In addition, major secondary metabolites from four fungi were identified as penicillic acid, patulin, pseurotin A, and javanicin. Epigenetic modifiers and minerals induce significant changes in the profile of the secondary metabolites. Their usage combined with microscale fermentation provides a cost-efficient tool for exploring fungal secondary metabolism.